Comparative Analysis of Islamic and Conventional Economic, Banking and Microfinance System (Journal of Asian Development Studies, 2025)
This research aims to provide a comprehensive and comparative analysis of Islamic and conventional approaches to economics, banking and microfinance, drawing from a set of peer reviewed academic articles published between 2008 and 2024. This Islamic economic model is rooted in Shariah Law, emphasising equity, justice, risk sharing, and the prohibition of riba (interest), while the interest-based financial system, capital accumulation, and technological advancement drive the other, conventional model. The analysis investigates five dimensions, as follows: the economic growth model (using Indonesia as a case study), banking practices (profit sharing vs. interest rate), the financial performance of Islamic versus conventional banks in Pakistan, microfinance approaches to poverty alleviation, and the ethical foundation of the financial system. Findings show that the Islamic system excels in social equity, financial inclusion, and resilience. At the same time, other conventional systems offer higher profitability and scalability but also face criticism for exacerbating inequality and exclusion. The integration of Islamic principles into the existing financial framework could offer a more ethical, inclusive, and sustainable model for economic development, particularly in emerging economies. This paper advocates for a hybrid financial ecosystem and offers policy recommendations for sustainable growth, aligning with the Sustainable Development Goals (SDGs).